A Second Order Method for the Linearly Constrained Nonlinear Programming Problem - McCORMICK, GARTH P. (Nonlinear Programming, 1970)
An algorithm using second derivatives for solving the problem: minimize f(x) subject to Ax − b ≥ 0 is presented. Convergence to a Second-Order Kuhn Tucker Point is proved. If the strict second-order sufficiency conditions hold, the rate of convergence of the algorithm is shown to be superlinear or even quadratic with aLipschitz condition on the second derivatives of f(x).